2006
DOI: 10.1177/0730888405280160
|View full text |Cite
|
Sign up to set email alerts
|

Occupational Networking as Normative Control

Abstract: With workforce flexibility and nonstandard, "contingent," work have come new mechanisms for labor market mediation and workforce control. This study examines occupational connection and control in two groups of contract professionals. For these occupational practitioners, networking is a mechanism for labor market regulation as well as for finding work. Networking perpetuates occupational norms that demand commitment to work, accountability to clients, and reciprocity among colleagues. Adhering to occupational… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(10 citation statements)
references
References 39 publications
(39 reference statements)
0
10
0
Order By: Relevance
“…Research on social capital has demonstrated that trusted social networks can provide individuals with information of higher quality, business referrals and some social control (Granovetter 1995;Yakubovich and Kozina 2000;Yakubovich 2005). The literature of professional contracting also stress the important role of social networks in terms of risk coping strategies (Barley and Kunda 2004;Osnowitz 2006;Antcliff, Saundry, and Stuart 2007;Apitzsch 2010). Our study investigates whether such social capital findings are relevant to freelancers contracting on the Internet.…”
Section: The Studymentioning
confidence: 99%
“…Research on social capital has demonstrated that trusted social networks can provide individuals with information of higher quality, business referrals and some social control (Granovetter 1995;Yakubovich and Kozina 2000;Yakubovich 2005). The literature of professional contracting also stress the important role of social networks in terms of risk coping strategies (Barley and Kunda 2004;Osnowitz 2006;Antcliff, Saundry, and Stuart 2007;Apitzsch 2010). Our study investigates whether such social capital findings are relevant to freelancers contracting on the Internet.…”
Section: The Studymentioning
confidence: 99%
“…They overwhelmingly reported that advertising had been useless in generating business, suggesting the absence of a preexisting market. The ICEA is of little use here; although the organization attempts to help raise the profile of the industry in general, as a national and regional entity without a significant presence at the local level, it does not appear to produce new clients or particularly useful networks (Davis, Renzulli, & Aldrich, 2006;Osnowitz, 2006).…”
Section: Obstacles To Legitimacymentioning
confidence: 99%
“…The market shelter has thus focused the forensic field on local concerns. In the long term, however, these strong protections have worked conservatively-stifling innovation, professional consolidation, scientific knowledge, and a diversification of skill-sets, audiences, and resources-and rendered the field highly vulnerable (for similar tensions in contingency work, see Osnowitz, 2006). Structural barriers to change are also not beneficial for the state or general public because these parties receive medical knowledge increasingly focused only on criminal justice rather than a broader set of public concerns.…”
Section: The Market Shelter: a Perch Or A Bunker?mentioning
confidence: 99%
“…Yet, at the broader societal level and to various audiences, professionals made the case that their power rested on a superior scientific or technical competency. Professionals legitimate their mandate with the expectation to adhere to self-defined standards of practice (Osnowitz, 2006). As we know from various professional socialization studies, every profession depends on abstract knowledge that forms the core of its expertise and to be a professional implies that one applies this knowledge appropriately (Atkinson, 1984;Becker, Geer, Hughes, & Strauss, 1961;Fox, 1957;Light, 1979).…”
mentioning
confidence: 99%
See 1 more Smart Citation